An experimental investigation on the performance and emission characteristics of a twin cylinder DI compression ignition engine employing bio-diesel blend as fuel at different injection timings and injection pressures. (27th June 2011) - Pandian, M.; Sivapirakasam, S.P.; Udayakumar, M.
In this study, the combined effect of injection timing and injection pressure on the performance, emission characteristics of a twin cylinder CIDI engine employing biodiesel blend of B40 as fuel was evaluated. The vegetable oil is extracted from the pongamia seeds which further underwent the transesterification process to get converted into biodiesel. The experiments were carried out at different injection timings of 18, 21, 24, 27 and 30° BTDC and at the injection pressures of 150, 175, 200, 225 and 250 bar. The best performance and lower CO, HC and smoke emissions were obtained at 225 bar and at 30° BTDC but NOx emission was higher. Considering lower NOx emission and better performance, the 225 bar of injection pressure and 21° BTDC of injection timing can be set as the optimum value for the specified twin cylinder diesel engine.